Pengaruh Nilai Tukar, Volume Ekspor Dan Bea Keluar Terhadap Harga Ekspor Pinang (Studi Kasus Pada Perusahaan Eksportir Cv.Mulia Karya Medan) - Maysarah, Siti; Rokan, Mustafa Kamal; Marliyah, M (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
The theory of the law of demand States that when prices go up then the demand for such items will decrease, and vice versa, but actually this theory does not apply to the export price the export prices caused the betel nut betel nut fluctuating. At observing the start of export prices cause suspected pinang fluctuating due to changes in exchange rates, the volume of exports, and bea came out. This research aims to know and explain the influence of the variable exchange rates, the volume of export and customs out simultaneously against the export price of betel nut on CV exporter company. The noble work of the terrain and the influence of the exchange rate, the volume of export and customs out partially against the export price. This type of research is research with quantitative approach. The variables used in this study is the exchange rate, the volume of export and customs came out as export prices and free variable pinang as variables are bound. This study uses secondary data using time series (time series) data per month during the period from 2013 to 2018. Methods of data analysis used was multiple linear regression analysis using Reviews program 8. Multiple linear regression analysis results indicate that the presence of influence simultaneously between the variable exchange rates, export volume and export price out against bea pinang, partially contained positive influence between Exchange rates and export volume against the export price of betel nut, and there is the influence of the negative influences of customs between partially out against export price the exporter company pinang CV. Noble work of Medan.